Screening of Relevant Genes and Signalling Pathways Affecting Adult Urosepsis: A Bioinformatic Analysis - Shi, Xu Xi; Rong, Lu Rong; Wei, Huang Zhong (Urology Journal, 2025)
Purpose: The cellular and molecular pathophysiology of urosepsis, a condition caused by a urinary tract infection spreading to the bloodstream, involves complex epigenetic behavior. The objective of this study was to identify relevant genes and signaling pathways in adult urosepsis through a bioinformatic analysis of differentially expressed genes (DEGs). Materials and Methods: In this in silico study, the GSE69528 dataset, containing 138 total RNA blood samples from patients with sepsis and uninfected controls, was obtained from the Gene Expression Omnibus (GEO) database. Microarray data were analyzed using GEO2R tools and R software. DEGs were identified using a fold change (FC) cutoff of > 1.5 or < 0.67 and a significance level of p < 0.05. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were used to determine the enriched pathways of DEGs before constructing protein-protein interaction (PPI) networks with STRING and Cytoscape. Results: A total of 108 DEGs were identified, comprising 67 upregulated and 41 downregulated genes. GO and KEGG analyses revealed that these DEGs were significantly enriched in pathways such as the complement and coagulation cascade, neutrophil degranulation, negative regulation of interferon-gamma response, T-cell activation, and granulocyte differentiation. The PPI network analysis identified 67 nodes with 110 interactions, from which CEACAM8, MPO, and RETN were identified as hub genes. Overexpression of CEACAM8 and MPO and suppression of RETN may be associated with a better disease prognosis. Conclusion: The identified hub genes—CEACAM8, MPO, and RETN—are predicted to be significant biomarkers in the prognosis and progression of sepsis. These genes could be targeted for the discovery of new therapeutic drugs for treating and managing urosepsis.